Longer-Term Omega-3 LCPUFA More Effective Adjunct Therapy for Tuberculosis Than Ibuprofen in a C3HeB/FeJ Tuberculosis Mouse Model - Hayford, Frank E. A.; Ozturk, Mumin; Dolman, Robin C.; Blaauw, Renee; Nienaber, Arista; Loots, Du Toit; Brombacher, Frank; Smuts, Cornelius M.; Parihar, Suraj P.; Malan, Linda (Frontiers in Immunology, 2021)
Advancement in the understanding of inflammation regulation during tuberculosis (TB) treatment has led to novel therapeutic approaches being proposed. The use of immune mediators like anti-inflammatory and pro-resolving molecules for such, merits attention. Drug repurposing is a widely used strategy that seeks to identify new targets to treat or manage diseases. The widely explored nonsteroidal anti-inflammatory drug (NSAID) ibuprofen and a more recently explored pharmaconutrition therapy using omega-3 long-chain polyunsaturated fatty acids (n-3 LCPUFAs), have the potential to modulate the immune system and are thus considered potential repurposed drugs in this context. These approaches may be beneficial as supportive therapy to the already existing treatment regimen to improve clinical outcomes. Here, we applied adjunct ibuprofen and n-3 LCPUFA therapy, respectively, with standard anti-TB treatment, in a C3HeB/FeJ murine model of TB. Bacterial loads, lung pathology, lung cytokines/chemokines and lung lipid mediators were measured as outcomes. Lung bacterial load on day 14 post-treatment (PT) was lower in the n-3 LCPUFA, compared to the ibuprofen group (p = 0.039), but was higher in the ibuprofen group than the treated control group (p = 0.0315). Treated control and ibuprofen groups had more free alveolar space initially as compared to the n-3 LCPUFA group (4 days PT, p= 0.0114 and p= 0.002, respectively); however, significantly more alveolar space was present in the n-3 LCPUFA group as compared to the ibuprofen group by end of treatment (14 days PT, p = 0.035). Interleukin 6 (IL-6) was lower in the ibuprofen group as compared to the treated control, EPA/DHA and untreated control groups at 4 days PT (p = 0.019, p = 0.019 and p = 0.002, respectively). Importantly, pro-resolving EPA derived 9-HEPE, 11-HEPE, 12-HEPE and 18-HEPE lipid mediators (LMs) were significantly higher in the EPA/DHA group as compared to the ibuprofen and treated control groups. This suggests that n-3 LCPUFAs do improve pro-resolving and anti-inflammatory properties in TB, and it may be safe and effective to co-administer as adjunct therapy with standard TB treatment, particularly longer-term. Also, our results show host benefits upon short-term co-administration of ibuprofen, but not throughout the entire TB treatment course.